Anchoring and packing of self-assembled monolayers of semithio-bambusurils on Au(111). Issue 2 (24th December 2019) - Kunturu, Pramod Patil; Kap, Özlem; Sotthewes, Kai; Cazade, Pierre; Zandvliet, Harold J. W.; Thompson, Damien; Reany, Ofer; Huskens, Jurriaan
Abstract : Self-assembled monolayers have been formed of semithio -bambusurils that undergo conformational changes to direct all S atoms to the gold surface. Abstract : Semithio -bambusurils are a unique family of anion-binding host macrocycles that form self-assembled monolayers (SAMs) on Au(111). SAMs of semithio -bambus[ n ]uril homologs with different cage sizes (1: n = 4; 2: n = 6) have been investigated using electrochemistry, X-ray photoelectron spectroscopy (XPS), scanning tunneling microscopy (STM), and molecular dynamics (MD) simulations. Electrochemical measurements showed that electron transfer occurs via tunneling through the SAMs, and the low resistivity indicated an open layer architecture. XPS confirmed that thiocarbonyl sulfur atoms are chemisorbed to the Au(111) surface, and STM revealed the formation of ordered domains in a rectangular lattice for 1 and a highly ordered triangular/hexagonal lattice for 2. MD simulations substantiated the STM data by quantifying the balance between molecule–surface bonding, molecular conformations, and supramolecular packing that drive the formation of SAMs that maximize their surface coverage within the limits of conformational strain.